Activation of PPARγ Protects Obese Mice from Acute Lung Injury by Inhibiting Endoplasmic Reticulum Stress and Promoting Mitochondrial Biogenesis - Tang, Yin; Wei, Ke; Liu, Ling; Ma, Jingyue; Wu, Siqi; Tang, Wenjing (PPAR Research, 2022)
Objective. Obesity-induced endoplasmic reticulum (ER) stress plays a role in increased susceptibility to acute lung injury (ALI)/acute respiratory distress syndrome (ARDS). The activation of peroxisome proliferator-activated receptor-γ (PPARγ) is associated with lung protection and is effective in ameliorating ER stress and mitochondrial dysfunction. The aim of this study was to investigate the expression of PPARγ in the lung tissues of obese mice and explore whether the PPARγ-dependent pathway could mediate decreased ALI/ARDS by regulating ER stress and mitochondrial biogenesis. Methods. We determined PPARγ expression in the lung tissues of normal and obese mice. ALI models of alveolar epithelial cells and of obese mice were used and treated with either PPARγ activator rosiglitazone (RSG) or PPARγ inhibitor GW9662. Lung tissue and cell samples were collected to assess lung inflammation and apoptosis, and ER stress and mitochondrial biogenesis were detected. Results. PPARγ expression was significantly decreased in the lung tissue of obese mice compared with that in normal mice. Both in vivo and in vitro studies have shown that activation of PPARγ leads to reduced expression of the ER stress marker proteins 78-kDa glucose-regulated protein (GRP78), C/EBP homologous protein (CHOP), and Caspase12. Conversely, expression of the mitochondrial biogenesis-related proteins peroxisome proliferator-activated receptor γ coactivator 1 (PGC-1α), nuclear respiratory factor-1 (NRF-1), and mitochondrial transcription factor A (TFAM) increased. Furthermore, activation of PPARγ is associated with decreased levels of lung inflammation and epithelial apoptosis and increased expression of adiponectin (APN) and mitofusin2 (MFN2). GW9662 bound to PPARγ and blocked its transcriptional activity and then diminished the protective effect of PPARγ on lung tissues. Conclusions. PPARγ activation exerts anti-inflammation effects in alveolar epithelia by alleviating ER stress and promoting mitochondrial biogenesis. Therefore, lower levels of PPARγ in the lung tissues of obese mice may lead to an increased susceptibility to ALI.